DUKUNGAN KELUARGA TERHADAP MEKANISME KOPING PADA PASIEN PASCA STROKE : LITERATURE REVIEW - Cavin Maulana; Wasisto Utomo; Ari Pristiana Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Stroke is the symptoms that occur because of disruption of blood supply to the brain caused by broken or blocked blood vessels. general signs that happens in post-stroke patients such us will be changes in one side of the body, difficulty in speaking, walking, and loss of consciousness. This incident will affect personal life and dependence on others, especially family. Positive family support will affect the feelings and responsss of patients to the health conditions which called coping macanism. To determine family support with coping mechanism of post-stroke patients. The method used is a literature review study obtained from searching research articles using the keywords Family Support AND Post-Stroke OR Coping Mechanisms AND Post-Stroke according to the inclusion criteria is articles published in 2016-2020. Data Source: GoogleSchoolar, Semantic Schoolar. Based on 6 reviewed journals obtained 4 of journals discussing family support in stroke patients, informational and emotional support is the most commonly received support of patients, 1 journal discussing coping mechanisms in stroke patients states that more than half of stroke patient respondents have maladaptive coping mechanisms, 1 journal discussing family social support interventions affecting the improvement of adaptive coping mechanisms. Based on the literature review of 6 journals found family support is very important for coping mechanisms of patients after stroke. Keyword: coping mechanisms; family support;and post stroke